2014
DOI: 10.1186/2050-7283-2-18
|View full text |Cite
|
Sign up to set email alerts
|

A mediation model of mindfulness and decentering: sequential psychological constructs or one and the same?

Abstract: BackgroundMindfulness and decentering are closely related processes both assumed to promote well-being. While some researchers claim that mindfulness and decentering can be clearly differentiated others suggest to use these concepts interchangeably. The precise relation between mindfulness and decentering remains unclear and therefore the present study aims to determine the relation between mindfulness and decentering.MethodsIn a structural equation modeling framework, a mediation model was tested among a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 56 publications
3
38
0
2
Order By: Relevance
“…Meanwhile, in the group without depressive symptoms results show greater improvement over the other two groups showing changes in variables of mindfulness (observe, describe, no judgment) and decentering. These results show that the intervention in mindfulness improves certain metacognitive skills and are consistent with some studies indicating increases in decentering after mindfulness intervention (Bieling et al, 2012;Getch et al, 2014;Hargus et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, in the group without depressive symptoms results show greater improvement over the other two groups showing changes in variables of mindfulness (observe, describe, no judgment) and decentering. These results show that the intervention in mindfulness improves certain metacognitive skills and are consistent with some studies indicating increases in decentering after mindfulness intervention (Bieling et al, 2012;Getch et al, 2014;Hargus et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, metacognitive skills seem to be related to the development of the capacity to put mental contents in another perspective or accept one's needs (Aldao et al, 2010;Garnefski et al, 2001). These abilities allow people to meet their necessities more accurately or connect with alternative meanings gaining new strengths (Getch et al, 2014). This flexibility to face adversities transforms them in a possible source of personal growth, also known as resilience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Decentring in mindfulness aims to reduce participants’ experiences of avoidance, allowing them to turn towards and accept distressing thoughts and feelings. Previous studies have also shown that decentring acted as a mediator of mindfulness interventions in improving psychological well‐being (Josefsson, Lindwall, & Broberg, ), depressive symptoms (Bieling et al ., ; Gecht et al ., ; Hargus, Crane, Barnhofer, & Williams, ), and anxiety (Hayes‐Skelton & Graham, ; Hoge et al ., ). Here, we showed that decentring may mediate the relationship between mindfulness and emotional distress in people with MS, and it is something that might change quicker than acceptance.…”
Section: Discussionmentioning
confidence: 97%
“…The number of mindfulness measures that exist and are used in different studies further complicate this problem. For example, Gecht et al 23 While it is advantageous to have different scales to measure a construct, the same advantage becomes a problem when each measure conceptualizes the construct being measured differently. Mindfulness is treated by some as a technique, by some as a naturally occurring trait and as a state to be cultivated by yet others.…”
Section: Discussionmentioning
confidence: 99%